Investigations on the occurrence of a muscular disorder in Austrian slaughter pigs - Lukas Schwarz; Carolin Schöner; Rene Brunthaler; Herbert Weissenböck; Tanja Bernreiter-Hofer; Barbara Wallner; Andrea Ladinig (Porcine Health Management, 2021)
Abstract Background In slaughterhouse, veterinarians responsible for meat inspection are often confronted with abnormalities in carcasses, not only in pigs but in all livestock species. In 2017, a veterinarian responsible for meat inspection in a slaughterhouse in Styria, Austria, observed gluteal muscles infiltrated by fat and muscle tissue obviously being replaced by fat in two different slaughter pigs. These muscles were sent for further diagnostics to the University Clinic for Swine. Results The two muscle samples were investigated histopathologically and diagnosed with fatty muscular dystrophy. The results of routine histopathology were confirmed by dystrophin-specific immunohistochemistry. Sex of the two affected animals was determined retrospectively using a PCR-based protocol and resulted in one male and one female pig. A survey to determine the prevalence of fatty muscular disorders of pork revealed that this phenomenon gets frequently observed in Styria, but also occurs in Upper Austria and Lower Austria. Mostly gluteal and lumbal muscles were affected and approximately 20–40% of the affected muscles were replaced by fat. Conclusions Fatty muscular dystrophy or muscular steatosis, as it was sometimes called in early literature, seems not to be an uncommon and rare event and is known to have several different causes. As it was detected in both sexes, our observations are different to the described case in Japan, where only one male individual was affected. To avoid further increase of such cases (fatty muscular dystrophy), it would be useful to clarify the cause. First, whether the cause is environmental or genetic, and in case it is genetic it would be key to disentangle the underlying genomic architecture. Having causal variants described—one could think about integrating this information (depending on the mode of inheritance and the number of loci involved) in the breeding program of pigs. Furthermore, the proportion of non-Austrian pig genetics used for commercial pig production in Austria should be reviewed in order to be able to make reliable statements about the spread of the disease not only in Austrian pig breeds, but also in pig breeds worldwide.